OPTIMIZING CAPITAL MANAGEMENT STRATEGIES TO INCREASE COMPANY COMPETITIVENESS IN THE GLOBAL MARKET - Rico Nur Ilham; Irada Sinta; Frengki Putra Ramansyah; Putri Miranda Sembiring; Dilla Ramadani (RADJA PUBLIKA, 2026)
This study explores the role of capital management strategies in enhancing the competitiveness of companies in the global marketplace. In a rapidly evolving and increasingly interconnected global economy, businesses face significant challenges in maintaining financial stability and gaining a competitive edge. Capital management, which encompasses strategies related to working capital management, risk mitigation, investment decisions, and financial structuring, is essential for sustaining long-term growth and operational efficiency. The research employs a mixed-methods approach, combining qualitative data from semi-structured interviews with key financial decision- makers and quantitative data from a survey of 200 business professionals. The findings reveal that companies that optimize their working capital, actively manage risks through hedging and diversification, strategically invest in emerging markets, and maintain a balanced financial structure are more likely to perform better and sustain a competitive advantage in global markets. The analysis indicates that shorter cash conversion cycles, the use of risk management tools, investment in high-growth regions, and maintaining an optimal capital structure all positively correlate with improved financial performance and market share. This study provides a comprehensive framework for companies to enhance their capital management practices and improve their competitiveness on the global stage. By focusing on strategic capital allocation and efficient resource utilization, businesses can navigate the challenges of globalization, maximize profitability, and secure long-term success in an increasingly competitive environment.